2011
DOI: 10.1177/1403494811420324
|View full text |Cite
|
Sign up to set email alerts
|

Daily steps among Finnish adults: Variation by age, sex, and socioeconomic position

Abstract: We conclude that about one-quarter of men and one-fifth of women are considered as inactive, based on the number of daily total steps. Our results suggest that total steps may provide a very different picture of activity from aerobic steps; important differences are evident by socioeconomic position and day of the week.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
38
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 21 publications
(57 reference statements)
3
38
2
1
Order By: Relevance
“…Colbert et al [9] has reported significant correlations between the pedometer and armband step counts (r = 0.87). Similarly, in a previous study, a high correlation (r = 0.94, p < 0.001) was found between measurements made by an accelerometer and pedometer [26]. Some possible explanations for the differences between the findings of our study and those of previous studies include different numbers of participants, different occupational domains of the participants and differences in the measurement tools used (brands and features).…”
Section: Discussioncontrasting
confidence: 53%
See 2 more Smart Citations
“…Colbert et al [9] has reported significant correlations between the pedometer and armband step counts (r = 0.87). Similarly, in a previous study, a high correlation (r = 0.94, p < 0.001) was found between measurements made by an accelerometer and pedometer [26]. Some possible explanations for the differences between the findings of our study and those of previous studies include different numbers of participants, different occupational domains of the participants and differences in the measurement tools used (brands and features).…”
Section: Discussioncontrasting
confidence: 53%
“…These values are similar to the values obtained in the overall European population. Studies have shown that the average daily number of steps -7854 in Turkey, 9655 in Belgium, 10 617 in Sweden, and 9500 in Finland − vary from country to country because of differences in climate conditions, transportation, pavement, roads and cultural factors [7,26]. Similarly, Thompson et al [27] reported an average daily number of steps in women of 8354 and that the number of steps was lower among middle-aged women than among younger women.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Those individuals who completed the pedometer study were more often women (p < 0.001) and had a higher level of education (p = 0.002). The level of self-rated PA did not differ significantly from those who did not participate in the pedometer study (Hirvensalo et al, 2011). After removing those with missing or incomplete data, information on 1853 participants was included in this study.…”
Section: Participantsmentioning
confidence: 99%
“…were disabled and unable to work, and 8% remained home with their children or (Hirvensalo, Telama, Schmidt, Tammelin, Yang, Magnussen et al, 2011).…”
Section: Participantsmentioning
confidence: 99%